Contemplation of food industry attributes confronted in smooth adoption of Lean Six Sigma practices. (11th July 2022) - Sharma, Janpriy; Tyagi, Mohit; Panchal, Dilbagh; Singh, Ravi Pratap
Food industries feed the lives on earth for survival and have significant importance in the economy of the country too. Globalisation, the growing population across the world, has increased the demand for food commodities, and industries are burdened with the pressure of high production volumes of quality products. Hence, the need of the hour becomes that industries should deploy various quality improvement initiatives like Lean Six Sigma (LSS), to improve their production practices and outputs with increased profitability. Food industries are quite different from other manufacturing industries in terms of product type, processes, procurement and distribution channels, etc. Likewise, the deployment of LSS principles in food industries is also monitored by its special attributes. These attributes must be identified before the successful implementation of LSS in food industries. This work identifies those unique attributes of food industries that act as barriers to the smooth deployment of LSS. The identified attributes are further analysed by the tool of grey-decision-making trial and evaluation laboratory (DEMATEL). The results from this study enable the industry to curb the attributes which are causing the barrier in implementing LSS. For checking the robustness of the generated results, sensitivity analysis is carried out.